Transformed section method for estimating the effective tensile modulus derived from compression test and four-point bending test results for modeling of bamboo material - Salamero, Jayson Y.
Bamboo as a construction material has been used in various applications. Despite of the known advantages in using bamboo compared to conventional materials such as steel and concrete, its widespread use is still hindered due to insufficient engineering knowledge on this material and its properties. Various physical and mechanical test standards are being proposed and standardized. Several studies are also being conducted to be able to gain more knowledge on this material. Compression, tension and bending test results are the common properties being reported by many studies. Among these tests, the tens ile test is commonly mentioned as the most difficult to conduct due to problems on handling and loading the specimen. It is the intent of this study to provide a method for estimating the effective tensile modulus of bamboo provided that compression and bending tests are conducted. In this method, the transformed section of a bamboo beam subjected to constant bending moment is analysed using basic principles of mechanics. The moduli ratio between the tensile modulus and compression modulus is used to convert the area in tension to an equivalent area having the same material property as those in compression. The strain or displacement of the resu lting homogeneous beam section is calculated and compared to the bending test results. The moduli ratio that results in agreement between the model and the test strain or displacement is the factor used to determine the effective tension modulus. Test data available in the literature were used to demonstrate the procedure. The values of the moduli ratio from the data used range from 1.0 to 1. 78 . Finite Element Method (FEM) modeling was also performed assuming isotropic material with different compression and ten sion moduli to validate the derived results and to show the stress and strain di stribution on a beam model.